3(x-1)+2(x-2)=x+1

Simple and best practice solution for 3(x-1)+2(x-2)=x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)+2(x-2)=x+1 equation:



3(x-1)+2(x-2)=x+1
We move all terms to the left:
3(x-1)+2(x-2)-(x+1)=0
We multiply parentheses
3x+2x-(x+1)-3-4=0
We get rid of parentheses
3x+2x-x-1-3-4=0
We add all the numbers together, and all the variables
4x-8=0
We move all terms containing x to the left, all other terms to the right
4x=8
x=8/4
x=2

See similar equations:

| -130=-5(4a-2) | | (2x-13)+(4x-5)=90 | | 16=d+9 | | 2(3x)+5x-6=27 | | z=450+135 | | 5(x-1)-14=-24 | | z=450-135 | | r+14=18 | | 5x=80.75 | | z-135=450 | | -9{x+3}=18 | | 1/4^2x+3=32 | | X+18=38x | | 3x7x+17=4x | | (X-4)(x-5)=(x-4)(2x+3)=0 | | z+135=450 | | X+18=36x | | (7x+15)+(x+13)=180 | | 12x-20=220 | | 6x+10+7x=180 | | 6x=9/2x+15 | | -3(2x-6)=-18 | | 100=X+24x | | 7x-3+5x=-3 | | x-11=4x+26 | | 2x=x+4= | | (1x+9)+(2x+6)=180 | | 3(2r-5)=27,2r5 | | |8y+4|=2|y−1||8y+4|=2|y−1| | | 10x+40/6=50 | | 5g=-55 | | 5n+-2n=-3n |

Equations solver categories